The Organizational Justice of the Administrative Leaders and its Impact on Employees’ Career Performance - Al-Dulaimi, Zaid Yaseen Saud (Journal of Economic Development, Environment and People, 2017)
Abstract. The aim of this study is to help us to know the degree of Organizational Justice practiced by the administrative leaders in Baghdad for Economic Sciences and of Al-Ma’mun privet university colleges in Baghdad and its relationship to the employees’ work or Career Performance. In order to achieve this goal, the study will seek to answer the following questions: What is the degree of Organizational Justice practiced by the administrative leaders in the discussed colleges from the employees’ point of view? What is level of work or Career Performance of employees from the point of view of their leaders? The study’s society is formed from administrative leaders, heads of departments and discussed faculties. Researchers will use a questionnaire for data collection and it will include, the responder’s demographic information, the measuring tool for the Organizational Justice practiced by the administrative leaders, the measurement of Career Performance of their employees. Study Tools has been verified by bringing it to the attention of the arbitrators of jurisdiction, and verification of the appropriateness of using the test method and the test. For answering the questions of the study researchers will use arithmetic averages, standard deviations and Pearson Linklabs.